Formulasi dan evaluasi sediaan hand cream ekstrak etanol brokoli (Brassica oleracea L.) - Silvy Aldila; Veronica Bellacaesa; Tunik Saptawati; Rissa Maharani Dewi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Broccoli (Brassica oleracea L.) extract contains flavonoid compounds and vitamin C. Vitamin C has a protective role against free radicals, brightens skin tone, and enhances sensitivity to keep skin moist. The content of broccoli is very suitable for preparation in hand cream preparations with moisturizing function for dry skin, especially hand skin, because hand skin only has endocrine sweat glands, so it is easy to water. to handle. evaporation (transepidermal water loss) occurs. In this study, three formulations of hand cream were made with three concentration variants of broccoli extract, namely F1 (2g), F2 (3g) and F3 (4g). In addition, tests for the physical properties of the composition include sensory testing, homogeneity, pH, dispersion, adhesion and viscosity. The results showed that the formulas F1, F2 and F3 met the requirements of testing the mechanical and physical parameters of the preparation. The conclusion of this study was that the hand cream composition produced had an average pH value of 6, a dispersion of 5 cm, a adhesion of 3 s and a viscosity of 32000 cPs and was concluded to meet the requirements for physical characteristics.